Analyzing significance of variables influencing motorcyle road crash experience, frequency and severity - Uy, Francis Aldrine A. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
The total motorcycle road crash recorded in the Metro Manila Accident Reporting and Analysis System (MMARAS) database from 2005 to 2009 is 55, 169.00. The frequency of damage only to property and non-fatal crash in most cities are almost equal. Fatal road crashes can be noted to be approximately 2% of damage only or non fatal road crashes. MMARAS records revealed that motorcycle road crashes mostly involved cars. next to car, motorcycle is the second road user with the most number of crash involvements in the last five years. The total estimated cost of motorcycle related road crash in Metro Manila form 2005 to 2009 is estimated to have reached 12.15 Billion Pesos. Road crash records were acquired from MMARAS and the Traffic Accident Recording and Analysis System (TARAS) of the Department of Public Works and Highways (DPWH). Accomplished questionnaire survey forms 2,000 motorcycle riders and at least 600 other road users were collected. A total of 60 hours of video record on motorcycle operation along the top 5 roads with the highest motorcycle volume and top 5 roads with highest motorcycle road crash was collected and analyzed. In this study, the MMARAS and TARAS record where analyzed to generate a comprehensive analysis and report on the characteristics of motorcycle road crashes in Metro Manila and other selected cities in the Philippines. A comprehensive profile on rider characteristic and behavior was derived and analyzed from the result of the questionnaire survey. In includes rider's personal details, experience and training, road safety opinion, crash experience and anger and aggression score. Motorcycle operation like speed, space and relevant safety factors were observed and analyzed. Using fundamental statistical method, the most significant variables influencing motorcycle road crash experience, frequency and severity were identified and examined. The most significant factors that was found to influence road experience are rider's age, experience in years and aggression level. The significant factors that influence motorcycle road crash frequency are road geometry (number of lanes), motorcycle-car volume ration, motorcycle speed, average speed of other vehicles, riding habit score and aggression level. The most significant factors that influence crash severity considering riders characteristic and behavior are rider's age and experience in years, number of years with license, daily trip distance, and verbal aggression level. On road environment are time of the day, weather condition, junction type and control. The combined influence of road geometry (number of lanes) and motorcycle-car speed ratio was found to best estimate the road crash frequency and percentage of fatal, non-fatal and damage to property motorcycle road crash along the top roads considered for the study.
Thesis (Ph.D. Civil Engineering :Transportation)--University of the Philippines, Diliman
Keywords: Traffic accidents -- Philippines; Motorcycling accidents -- Philippines